2(x+4)-6=2

Simple and best practice solution for 2(x+4)-6=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+4)-6=2 equation:


Simplifying
2(x + 4) + -6 = 2

Reorder the terms:
2(4 + x) + -6 = 2
(4 * 2 + x * 2) + -6 = 2
(8 + 2x) + -6 = 2

Reorder the terms:
8 + -6 + 2x = 2

Combine like terms: 8 + -6 = 2
2 + 2x = 2

Add '-2' to each side of the equation.
2 + -2 + 2x = 2 + -2

Combine like terms: 2 + -2 = 0
0 + 2x = 2 + -2
2x = 2 + -2

Combine like terms: 2 + -2 = 0
2x = 0

Solving
2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| 9-9x=3c-9x | | 10(w+4)+4(W+4)+-6w=0 | | x+128=55 | | 3v+6=5v | | -29+11r+9n-2r-3n-11= | | 17s=-18+14s | | 12x-2=20x+4 | | 2+7cos(x)=4sin^2(x) | | M^2+6m+11=6 | | 12-4b=-8 | | 2w+2(3w+8)=28 | | 2=72/x | | y=x^3-9*x^2+24*x-18 | | 7p-9=-1+8p | | y-7/3=2 | | -6n+10=4-8n | | 10c=2+8c | | 3(b+3)+4(b+2)+b=89 | | 11=-3+z | | 24x+4=19x+4 | | 3x-(4x+6)=x-9 | | 11=-4.9t^2+120t | | 10x^2+12x-1=4x | | 8-(5/7)x-32 | | 2w+3(w+2)+2(w+5)=44 | | -10+k=10-9k | | -9j+10=10j | | -4a+16+6a=-9a | | (7x+3)(x-5)=-2x(5x+6)+x-19 | | -6-7f=-6f | | X-27=84 | | t-10=10-9t |

Equations solver categories